Workshop Pemanfaatan Artificial Intelligence untuk Merancang Pembelajaran Mendalam sebagai Upaya Peningkatan Kompetensi Guru di YAPIP Cianjur - Jainuddin, Jainuddin; Usman, Zea Zisman; Fineldi, Rira Jun; Nurfauziah, Puji; Anita, Ika Wahyu; Yolanda, Fitriana; Sthephani, Aulia; Siagian, Teddy Alfra; Jupri, Al; Sudihartinih, Eyus (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of educational technology requires teachers to possess adaptive skills in designing learning processes that meet the demands of the 21st century. Teachers at Yayasan Pendidikan Islam Pacet (YAPIP) in Cianjur face challenges in understanding and implementing deep learning approaches, which consist of mindful learning, meaningful learning, and joyful learning, as well as in utilizing Artificial Intelligence (AI) as an educational innovation. This community service program aimed to enhance teachers’ competencies through a workshop focused on integrating AI into the design of deep learning-based instruction. The method included four stages: planning, implementation, evaluation, and reflection, involving 28 teachers from elementary and junior high school levels. The results indicated improvements in teachers’ knowledge, skills, and attitudes toward AI integration, demonstrated by innovative lesson designs, group presentations, and reflective discussions. Evaluation revealed that more than 80% of participants reported increased confidence in applying AI to their teaching practice. Challenges included limited digital infrastructure and variations in teachers’ technological literacy. Nevertheless, the workshop proved to be an effective alternative solution for supporting curriculum implementation and strengthening teacher professionalism. The outputs included lesson plans, scientific publications, media articles, and recommendations for program sustainability. Thus, this activity is expected to serve as a replicable model for other schools to improve the quality of technology-based education in regions with low Human Development Index (HDI).